OP28 Host–microbial crosstalk in the pathogenesis of inflammation and cancer in primary sclerosing cholangitis. (25th January 2019) - Neyazi, M; Ilott, N; ,; Travis, S; Arancibia, C; Powrie, F; Geremia, A
Abstract: Background: Distinct inflammatory responses have been involved in primary sclerosing cholangitis-inflammatory bowel disease (PSC-IBD) and dysbiosis has been observed supporting a role for the microbiome in the pathogenesis of disease. We aimed to: (1) assess host–microbial functions in PSC-IBD (2) evaluate whether PSC-IBD-associated pathways affect epithelial transformation. Methods: Biopsies and mucosal brushings from colon and terminal ileum were collected from patients with PSC-IBD, ulcerative colitis without PSC (UC), and healthy controls (HC). 3′RNA sequencing was performed to analyse intestinal transcriptomes and 16S rRNA sequencing to characterise the adherent microbiome. Colonic crypts were isolated from biopsies, seeded onto basement membrane extract, and cultured in media containing growth factors to develop organoids. Organoids were stimulated with different cytokines for 24 h and markers of cytokine downstream pathways, stemness, and pluripotency were analysed by qPCR. Results: A distinct transcriptomic profile in the caecal biopsies of patients with PSC-IBD compared with UC and HC was identified (Figure 1, A left panel), with 890 genes being regulated in PSC-IBD (DESeq2 likelihood ratio test, adjusted p < 0.05). Amongst differentially regulated genes, we found an enrichment of pathways associated with cytokine signalling including IL22 and TGFβ (fold enrichment >2 and adjusted p < 0.05) (Figure 1A, right panel). We successfully cultured primary intestinal organoids from both groups of patients and HC (Figure 1B). Stimulation with IL22 or IFNγ resulted in STAT1 induction, and higher STAT3 induction was observed in PSC-IBD-derived organoids. Interestingly, expression of the IL22 receptor, IL22RA1, was induced by IFNγ stimulation in PSC-IBD-derived organoids that also over-expressed OLFM4 and POU5F1, both associated with pluripotency and early stages of neoplastic transformation (Figure 1C). Conclusions: The transcriptomic profile in the colonic mucosa of patients with PSC-IBD shows altered regulation of pathways previously associated with IL22 and TGFβ signalling. Both cytokines have been implicated in cancer pathogenesis. PSC-IBD-associated Th1 responses may result in increased epithelial IL22 responsiveness. Higher expression of the cancer stemness genes OLFM4 and POU5F1, triggered by bacteria and IL22 via STAT3 activation, suggest that microbial-driven IL22 responses may contribute to epithelial transformation.